Differences in Psychotropic Drug Prescribing Between Ethnic Groups of People with Dementia in the United Kingdom - Jones ME (Clinical Epidemiology, 2020)
Mary Elizabeth Jones, 1 Irene Petersen, 1 Kate Walters, 1 Cini Bhanu, 1 Jill Manthorpe, 2 Rosalind Raine, 3 Naaheed Mukadam, 4 Claudia Cooper 4 1Department of Primary Care and Population Health, University College London, London, UK; 2NIHR Health and Social Care Workforce Research Unit, King’s College London, London, UK; 3Epidemiology and Public Health, University College London, London, UK; 4Division of Psychiatry, University College London, London, UKCorrespondence: Claudia CooperDivision of Psychiatry, University College London, 6th Floor, Maple House, Tottenham Court Road, London W1T 7BN, UKTel +44 7759703235Email claudia.cooper@ucl.ac.ukPurpose: To test hypotheses that minority ethnic people with dementia in the UK receive fewer anti-dementia drugs and more psychotropic and anticholinergic drugs associated with harms.Patients and Methods: We analyzed UK primary care electronic health records from The Health Improvement Network (THIN) database (2014– 2016), comparing psychotropic drug prescribing initiation and duration between people with dementia from White, Black, and Asian ethnic groups. We repeated analyses in people (aged 50+) without dementia, to explore whether any differences found reflected prescribing patterns in the general older population, or were specific to dementia.Results: We included 53,718 people with and 1,648,889 people without dementia. Among people with dementia, compared to White ethnic groups, Asian people were less likely to be prescribed anti-dementia drugs when they were potentially indicated (adjusted prevalence rate ratio 0.86 (95% Confidence Interval 0.76– 0.98)), and received them for on average 15 days/year less. Compared to White groups, Asian and Black individuals with dementia were no more likely to take an antipsychotic drug, but those that had were prescribed them for 17 and 27 days/year more, respectively (190.8 (179.6– 199.1) and 200.7 (191.1– 206.5) days). Black people were less likely to be prescribed anxiolytics/hypnotics (0.60 (0.44– 0.8)), but the duration these drugs were prescribed was similar across ethnic groups. Asian people were more likely to be prescribed anticholinergic drugs (1.43 (1.19– 1.73)), in analyses unadjusted for cardiovascular comorbidities. Among people without dementia, those in the Asian and Black ethnic groups were less likely to be prescribed psychotropic drugs, relative to people from White groups.Conclusion: Among people with dementia, Asian groups received less potentially beneficial symptomatic treatments, and Asian and Black groups were prescribed antipsychotic drugs for longer than White ethnic groups. Our findings may indicate care inequalities.Keywords: ethnicity, prevalence rate ratio, medication, prescription duration